Clinical Autopsy. Benefits related to its practice - Javier Martínez Navarro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Clinical Autopsy is a tool of diagnostic confrontation which is decreasing worldwide in the last decades. In the University General Hospital Dr. Gustavo Aldereguía Lima in Cienfuegos, in spite of its own limitations, autopsy has achieved noticeable advances in quantity and quality at their application. The benefits obtained of these elevated rates reach positive impacts in medical assistance, teaching, research, health administration and society in general. The present work approaches the topic of clinical autopsy emphasizing on the benefits to the hospital institution related to the meetings linked to it as post mortem meetings, of death certification repairs, clinical pathological and mortality committees.